Factors influencing taxpayers to engage in tax evasion: Evidence from Woldia City administration micro, small, and large enterprise taxpayers - Erstu Tarko Kassa (Journal of Innovation and Entrepreneurship, 2021)
The main purpose of this paper is to investigate factors that influence taxpayers to engage in tax evasion. The researcher used descriptive and explanatory research design and followed a quantitative research approach. To undertake this study, primary and secondary data has been utilized. From the target population of 4979, by using a stratified and simple random sampling technique, 370 respondents were selected. To verify the data quality, the exploratory factor analysis (EFA) was conducted for each variable measurements. After factor analysis has been done, the data were analyzed by using Pearson correlation and multiple regression analysis. The finding of the study revealed that the relationship between the study independent variables with the dependent variable was positive and statistically significant. The regression analysis also indicates that tax fairness, tax knowledge, and moral obligation significantly influence taxpayers to engage in tax evasion, and the remaining moral obligation and subjective norms were not statistically significant to influence taxpayers to engage in tax evasion.
Keywords: 650; Moral obligation; Tax evasion; Tax fairness; Tax knowledge